The Effect of Ginger Water Decoction on Leg Edema in Pregnant Mothers at Kasih Ibu Primary Clinic, 2024 - Lubis, Basyariah; Wulandari, Suci; Safrida Nuzul Hayati (JURNAL KEBIDANAN KESTRA (JKK), 2024)
The bending of the uterus restricts venous return and gravitational pull, which increases fluid retention and causes 80% of pregnant women in the third trimester to experience leg edema or swelling. Edema in pregnant women’s legs can be a sign of dangerous pregnancy conditions, such as pre-eclampsia. Edema is also very dangerous for pregnant women as it can lead to issues with the heart, kidneys, and other body parts, disrupting their functions. Foot soaking, or foot hydrotherapy, is an additional therapy that can be done independently. To improve blood circulation and trigger a systemic response (vasodilation) through the dilation of blood vessels, bathing with warm water will help. The authors aim to conduct research on "The Effect of Ginger Decoction on Edema in Pregnant Women's Legs at Kasih Ibu Pratama Clinic in 2024" based on the above information and data. They believe that foot soaks can also be combined with other herbal ingredients. The research method used a population of 100 with a sample of 17 individuals, employing a quantitative research design and a one-group pre-test post-test model, where observations were made before and after treatment with data analysis using the Wilcoxon test. The study found that ginger decoction has an effect on reducing edema in the legs of pregnant women. The test results showed a probability of 0.01. This means that the probability < level of significance (? = 0.05), so Ha is accepted, and H0 is rejected, indicating a significant difference between leg edema in pregnant women before (pre-test) and after (post-test) the administration of ginger decoction. Therefore, ginger decoction has an effect on reducing edema in pregnant women's legs.